ANALISIS HUBUNGAN KEPATUHAN PENGOBATAN TERHADAP KONTROL GLIKEMIK PASIEN DIABETES MELITUS TIPE 2 DI INSTALASI RAWAT JALAN RUMAH SAKIT Ã¢â‚¬Å“XÃ¢â‚¬Â BULELENG - Pande Made Desy Ratnasari; I Gusti Ayu Indira Ardeliani; Agustina Nila Yuliawati (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2021)
Type 2 Diabetes mellitus (T2DM) is a chronic disease that requires long-term treatment. There were problems related to antidiabetic medication adherence. Medication adherence directly affects patientÃ¢â‚¬â„¢s blood glucose level. The aim of this study was to analyze the association between the medication adherence and glycemic control among T2DM patients. The study was an observational with cross sectional design. Participants were 90 of T2DM outpatient at Ã¢â‚¬Å“XÃ¢â‚¬Â Buleleng General Hospital in July-September 2020. T2DM patients were included if age ?18 years, received the same antidiabetic for three months before the study, sign informed consent, fill out the questionnare and have fully medical record data. Patient are excluded if having weak general condition, were pregnant or breastfeeding. Data was collected through interview using the Probabilistic Medication Adherence Scale (ProMAS) questionnaire and based on patientÃ¢â‚¬â„¢s medical records. Data were analyzed with Kruskall-Wallis test. The results showed that most of patients were male (55.6%), aged 46-65 years (61.1%), had DM for 5-10 years (46.7%), elementary school (37.8%), with comordbidities (50%) and without complications (77.8%). Majority of patients (42.2%) showed moderate-high medication adherence and the majority of patients (66.7%) has uncontrolled blood glucose. Based on statistical tests, there was no association between medication adherence with patientÃ¢â‚¬â„¢s glycemic control (p=0.168). In dispite of it, finding showed that the level of medication adherence had an impact on glycemic control. Patients with high medication adherence showed better glycemic control.